2020
DOI: 10.3389/fpsyg.2020.01371
|View full text |Cite
|
Sign up to set email alerts
|

Testing a Self-Compassion Intervention Among Job Seekers: Self-Compassion Beneficially Impacts Affect Through Reduced Self-Criticism

Abstract: Job search is associated with various obstacles and difficulties that can elicit negative emotions and undermine positive emotions. Having self-compassion may benefit job seekers' well-being by stimulating more balanced emotional responses to negative job search experiences. In an intervention study we examined whether state selfcompassion can be increased among job seekers through writing exercises in which job seekers are instructed to reflect with self-compassion on their negative job search experiences. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 64 publications
(156 reference statements)
2
3
1
Order By: Relevance
“…The large pre-to post-intervention increase in global state self-compassion aligns with previous research that has shown that self-compassionate reflective writing can be useful to increase state self-compassion in response to difficult experiences (Johnson & O'Brien, 2013;Kreemers et al, 2020;Moffitt et al, 2018Moffitt et al, , 2023Sirois et al, 2019). Also in line with the design of our intervention, the positive shift in state self-compassion was demonstrated across each of Neff's three domains of the self-compassion construct.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The large pre-to post-intervention increase in global state self-compassion aligns with previous research that has shown that self-compassionate reflective writing can be useful to increase state self-compassion in response to difficult experiences (Johnson & O'Brien, 2013;Kreemers et al, 2020;Moffitt et al, 2018Moffitt et al, , 2023Sirois et al, 2019). Also in line with the design of our intervention, the positive shift in state self-compassion was demonstrated across each of Neff's three domains of the self-compassion construct.…”
Section: Discussionsupporting
confidence: 87%
“…The large decrease in negative affect from pre-to post-intervention is also consistent with studies showing that self-compassionate reflective writing can help to mitigate negative emotional reactions in response to embarrassing and shameful experiences (Johnson & O'Brien, 2013;Kreemers et al, 2020;Leary et al, 2007;Sirois et al, 2019). We have extended these findings by demonstrating that online self-compassionate reflective writing can reduce negative affect amongst perinatal women in the context of thinking about challenges and difficult emotional experiences associated with the perinatal period.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Alternatively, the effects of problem-focused and solution-focused questioning techniques may outweigh each other in promoting or hampering action taking. While problem-focused questioning may cause deep reflection but also deactivating negative moods such as sadness and weariness (see Kreemers et al, 2020 ), solution-focused questioning may cause divergent thinking but also unrealistic fantasies that hinder the planning of concrete actions. Unlike concrete goals, positive fantasies lack a clear commitment to behavior ( Oettingen, 2012 ).…”
Section: Discussionmentioning
confidence: 99%